PREVALENCE OF ANTIMICROBIAL RESISTANCE AND CONTROL METHODS USED BY LIVESTOCK FARMERS AND VETERINARY SERVICE PROVIDERS IN KAYONZA DISTRICT TO IMPROVE ONE HEALTH IN RWANDA - Nadia Uwera, Maurice B. Silali, Laurien Ntamugabumwe (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Globally regionally and in Rwanda, the prevalence of antimicrobial resistance and the control strategies used by livestock farmers and veterinary service providers remain a big challenge to achieve in one health by population health on the health population, similar to Farmers in Kayonza District, it was this reasons led to study the prevalence of antimicrobial resistance and control methods used by livestock farmers and veterinary service providers in Kayonza district to improve one health in Rwanda, methods used were mixed of survey and interviews livestock farmers, veterinary doctors, community veterinary doctors as the target population utilizing descriptive, cross-sectional. Sampling techniques of purposive census, quota, and snowball sampling on the respective respondents. A sample size of 207 respondents was used. Data collection tools and instruments were key informant interviews KII, and focus group discussions, FGDs a mixed-method approach, incorporating both quantitative and qualitative research methods. Quantitative data was gathered using semi-structured questionnaires, while qualitative data was collected through Key Informant Interviews (KIIs) and Focus Group Discussions (FGDs). Data was managed, using SPSS Version 25 and, analyzed by tabulation of descriptive and inferential statistics, and presented in the form of pie charts and bar graphs. The results opined that in the prevalence of antimicrobials, 170 (82%), with RR of (0.643, 0. 233), signifying government protective strategies are active among the affected livestock farmers. While (37), 17.8%, opined that they are main cohorts of new antimicrobial resistance and in one health and death. And the majority of livestock farmers sell their livestock to butcher men in the community, before they die, thus evading mortalities of sick animals at home to control farmers’ loss of burying carcasses. Thus sell butchers who meet with residues of antibiotics of higher concentration to humans to consume so when they are administered drugs of low dosages they become resistant, has discussed in several KII with key stakeholders in Kayonza District. Therefore study on Antimicrobial resistance in Kayonza District looks forward to improving capacity building among population health through various integrated strategies of appropriate technologies to improve One Health outcomes.